Analisis Yuridis Akta Wasiat yang Melanggar Legitieme Portie: Implikasi Terhadap Tanggung Jawab Notaris - Septiana, Tri Wulan; Lontoh, Rielly; Turhamun, M. Slamet (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
This research is motivated by the existence of an inheritance dispute caused by the existence of a will deed made by a Notary that is contrary to the provisions of Legitieme Portie. In Article 913 of the Civil Code it is regulated that Legitieme portie must be given to the heirs in a straight line according to the law, against which the deceased person may not determine anything, even with a will deed. The formulation of the problem in this research is How is the notary's responsibility for a will that violates the absolute rights (Legitieme Portie) of the heirs in the Civil Code, and What are the legal consequences of a will deed that violates the absolute rights (Legitieme Portie) of the heirs in the Civil Code. The theory used in this research is the Theory of responsibility according to Hans Kelsen and the Theory of consequences according to Soeroso. The research method used in this study is normative juridical. Legal research is conducted by examining library materials or secondary data only. This study uses legislative, conceptual, analytical, and case-based approaches. The results of this study indicate that a notary who makes a deed contrary to the provisions of the Legitieme Portie is obliged to be held accountable under civil law. Although the court decision does not stipulate sanctions for notaries, if the notary is later sued by a party who feels aggrieved, the notary must be held accountable. The legal consequence of the will is that it is null and void and has no binding legal force.